Highly efficient oxygen evolution reaction via facile bubble transport realized by three-dimensionally stack-printed catalysts - Ye Ji Kim (Nature Portfolio, 2020)
Improved design of three-dimensionally nanostructured catalysts for oxygen evolution reaction (OER) can play a key role in maximizing the catalytic performance. Here, the authors show that woodpile-structured iridium consisting of 3D-printed, highly-ordered nanowire building blocks significantly improve OER mass activity.